Collaborative optimization between passive design measures and active heating systems for building heating in Qinghai-Tibet plateau of China. (March 2020) - Wang, Xiaoliang; Mai, Xianmin; Lei, Bo; Bi, Haiquan; Zhao, Bing; Mao, Gang
Abstract: Due to cold winter and cool summer in Qinghai-Tibet plateau, heating energy consumption accounts for a large proportion in the building energy consumption and reducing heating energy consumption is one of the main energy-saving methods for buildings. In the process of building heating, passive design measures and active heating systems (AHS) are always working together. To optimize the heating performance, it is necessary to coordinate the relationship between passive design measures and the AHS. However, it is impossible to obtain the specific quantitative optimized relationship between passive design measures and AHS based on existing research methods. To address this lack of knowledge, a collaborative optimization design method (CODM) is proposed in this paper to optimize the cost and the energy consumption of heating in the life cycle of the building. In CODM, comprehensive effects of passive design measures and the AHS on the total cost and the total energy consumption for building heating are analyzed. A railway passenger station is selected as a case study and results show that compared with initial design, the optimal total heating cost and total heating energy consumption for building heating can reduce 1948 ￥/m 2 and 2292 kW h/m 2 for the life cycle of the building, respectively. Highlights: A collaborative optimization design method (CODM) is proposed for building heating. Energetic and economic relationship of building heating are established. Optimizations between passive design measures and active systems are conducted.